IMPLEMENTASI NILAI-NILAI SPIRITUAL DAN MORAL DI LEMBAGA PENDIDIKAN - Andrini Lita Laksita; Nur Halimah; Dwi Noviani (LPPM Universitas Muhammadiyah Bulukumba, 2024)
Educational institutions not only function as a place for the transfer of knowledge, but also as a forum for character formation. This research aims to analyze how educational institutions carry out their role in instilling spiritual and moral values in students. Through literature studies and case analysis, this research reveals that the instillation of spiritual and moral values can be done through various means, such as integration in the curriculum, extracurricular activities, habituation of behavior, and teacher example. The results of the research show that the implementation of spiritual and moral values has a positive impact on the development of students, both internally cognitive, affective and psychomotor aspects. However, there are several challenges in implementation, such as lack of teacher understanding, lack of support from the school environment, and lack of systematic evaluation. Therefore, more comprehensive and sustainable efforts are needed to ensure the successful implementation of the values. spiritual and moral values in educational institutions.